Implementation of Guidance and Counseling Services in Addressing Student Behavior Regarding Family Economic Conditions at SMAN 1 Kedungwaringin - Divia Zahra Nuraulia; Azzahra Meitania Putri; Iis Izzatul Hasanah; Desandi Desandi; Nur Aini Farida (Penerbit Hellow Pustaka, 2025)
The purpose of this study is to examine how guidance and counseling services are implemented at SMA 1 Kedungwaringin to address student behavior influenced by family economic circumstances. A qualitative approach using a descriptive case study design is the methodology employed. Guidance and counseling teachers and two ninth-grade students who struggle with conduct because of financial strains in their families make up the research subjects. Sugiyono's interactive analysis methodology, which comprises data reduction, data presentation, and conclusion drawing, was used to examine the data that were gathered through documentation, in-depth interviews, and observation. The study's findings demonstrate that preventive and curative strategies, such as individual and group counseling, traditional services, and home visits, are used to provide advice and counseling services. This service's introduction has been shown to be successful in assisting students in coping with financial strains, boosting their drive to learn, and encouraging virtues like self-control, discipline, and responsibility. According to the study's findings, guidance and counseling services are crucial in helping students develop their moral fiber and mental toughness in the face of financial constraints in their families